QUANTIFICATION ET EVALUATION DE L’EROSION HYDRIQUE EN UTILISANT LE MODÈLE RUSLE ET DÉPOSITION INTÉGRÉS DANS UN SIG. APPLICATION DANS LE BASSIN VERSANT N'FIS DANS LE HAUT ATLAS DE MARRAKECH (MAROC) - Markhi, Amal; Laftouhi, Nour-Eddine; Soulaimani, Abderrahmane; Fniguire, Fatima (European Scientific Journal, ESJ, 2015)
Located in the High Atlas central-western, N'Fis basin shows a dissected topography, frequent and violent floods, and its characterization by a litho-stratigraphic succession from the Precambrian to the current that engender significant erosion, and cause reservoirs siltation. This study aims to map areas vulnerable to erosion in the N'Fis Basin, developed a Geographic Information System (GIS) into account soil types, networks of drainage and traffic direction integrating remote sensing and spatial data. The results highlight the hydrographic phenomena and their effects on water resources. To achieve the objective of calculating the RUSLE equation Factor, it was based on annual and monthly climate data, field missions, the digital elevation model and satellite imagery. The result indicates a change in the rate of erosion and the values are between 7t / ha / year downstream of the wadi N'fis and a maximum value 1221t / ha / year to non-arable areas and areas with strong slope values.